2017
DOI: 10.7567/jjap.56.04ck01
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photoemission and X-ray absorption spectroscopies of lithiated magnetite thin film

Abstract: Resonant photoemission spectroscopy (RPES) and X-ray absorption spectroscopy (XAS) were used to investigate the effect of lithiation on the electronic structure of Fe 3 O 4 thin film relevant to the operation mechanism of nanoionic devices to enable magnetic property tuning. Comparison of the Fe 2p XAS spectrum for lithiated Fe 3 O 4 (Li-Fe 3 O 4 ) with that for pristine Fe 3 O 4 clearly demonstrated that the number of Fe 2+ ions at octahedral B sites is increased by lithiation. The valence band RPES spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Figure b shows that the on-resonance VB spectra showed an intensity much higher than that of off-resonance VB spectra, regardless of the applied bias. This enhanced intensity proves the existence of Pr 4f states near the Fermi level, consistent with earlier results reported in ref . Taking a closer look at the line shape of the on-resonance data, we found that while there were no appreciable changes in on-resonance VB spectra at the Pr 3+ XAS maximum, clear changes in VB shapes as a function of applied bias were observed for spectra excited at the Pr 4+ absorption maximum, shown in Figure c.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Figure b shows that the on-resonance VB spectra showed an intensity much higher than that of off-resonance VB spectra, regardless of the applied bias. This enhanced intensity proves the existence of Pr 4f states near the Fermi level, consistent with earlier results reported in ref . Taking a closer look at the line shape of the on-resonance data, we found that while there were no appreciable changes in on-resonance VB spectra at the Pr 3+ XAS maximum, clear changes in VB shapes as a function of applied bias were observed for spectra excited at the Pr 4+ absorption maximum, shown in Figure c.…”
Section: Results and Discussionsupporting
confidence: 92%